PENGEMBANGAN MODEL LATIHAN DRIBBLE JUMP SHOOT CABANG OLAHRAGA BOLA BASKET PADA PELAJAR - Sabaruddin Yunis Bangun; Tarsyad Nugraha; Rian Handika (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This study aims to develop a dribble jump shoot training model in basketball. This type of research is research and development (Research and Development). In this development research, the product developed is a dribble jump shoot training model in basketball.The subjects in this research and development were 3 experts and 10 basketball athletes. The instruments used in this research and development were questionnaires and questionnaires used to collect data at the following stages: (1) needs analysis; (2) expert evaluation; (3) small group trials; and (4) field trials. The effectiveness test is the result of validation from 3 experts and the results of field tests. The results of the 3 experts stated that 86.25% was very suitable for use and the effectiveness test revealed a high gain value of 0.90. Based on the results of research and development, it can be concluded that: (1) By developing an exercise model dribble jump shoot This, can help students in improving basketball jump shoot skills. (2) Provide a new reference for basketball jump shoot practice.